Positive emotions are not simply the absence of the negative ones: Development and validation of the Emotional Recovery Questionnaire (EmRecQ) - Lundqvist, C.; Kentta, G. (The Sport Psychologist, 2010)
The purpose of this study was to psychometrically evaluate the Emotional Recovery Questionnaire (EmRecQ) and to describe athletes` individual response patterns in five repeated assessments using the EmRecQ. Three samples were used. Samples 1 and 2 consisted of 192 and 379 (Mean age 16.4 years, SD = 0.7 and Mean age:17.0 years, SD = 1.1) elite athletes from different sports. The third sample consistedof 20 (Mean age: 21.3, SD = 19.0) female elite basketball players. The EmRecQis a 22-item questionnaire that assesses Happiness, Security, Harmony, Love, and Vitality. Results showed acceptable weighted omega reliability and construct reliability. Confirmatory factor analyses supported the a priori specified five-factor correlated model. Case profiles of repeated assessments revealed individual response patterns of the separate EmRecQ subscales that corresponded well with rated training load and total quality of recovery. The findings provide support for the EmRecQ`s psychometric properties and applied usefulness.